1971
DOI: 10.1111/j.1348-0421.1971.tb00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Establishment of Lactobacilli in the Digestive Tract of Germ‐Free Chickens

Abstract: Establishment of lactobacilli in the digestive tract of germ-free chicks was studied using the organisms isolated from chickens, human infants and sour milk and those received from the American Type Culture Collection. In the case of monocontamination, intestinal lactobacilli such as Lactobacillus acidophilus, L. salivarius and L. It was shown that lactobacilli were predominant in the digestive tract of chickens [11,15], and the lactobacillus flora was composed mainly of Lactobacillus acidophilus, L. salivariu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 12 publications
1
25
1
Order By: Relevance
“…Recent studies have shown that Lactobacillus salivarius strains isolated from chicken gut could produce bacteriocins with antagonistic activity against Gram-positive bacteria (25). Morishita et al demonstrated that lactic acid bacteria are more effective for poultry when they have chicken origin (26). Therefore, administration of locally isolated strains will improve digestive gut micro flora as well as combat pathogen infection among birds.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Lactobacillus salivarius strains isolated from chicken gut could produce bacteriocins with antagonistic activity against Gram-positive bacteria (25). Morishita et al demonstrated that lactic acid bacteria are more effective for poultry when they have chicken origin (26). Therefore, administration of locally isolated strains will improve digestive gut micro flora as well as combat pathogen infection among birds.…”
Section: Discussionmentioning
confidence: 99%
“…It does suggest that the Lactobacilli in the developing intestinal flora exert a controlling effect on coliform bacteria. Several investigators observed increases in numbers of Lactobacilli accompanied by a decrease in coliforms after oral administration of L. acidophilus (Buchanan and Gibbons 1974;Fuller, 1973;Gilliland andSpeck, 1977 andMorishita et al, 1971). Several reports indicated greater declines in numbers of coliforms after feeding L. acidopbilus to humans (Muralidhara et al 1977;Speck, 1976).…”
Section: Colonization In Calf Intestinementioning
confidence: 99%
“…The inocula prepared were administered in 1-ml amounts to gnotobiotic chickens in the manner described in a previous paper [13].…”
Section: Animalsmentioning
confidence: 99%
“…The cecal contents were obtained from chickens sacrificed for examination at the age of about 4 weeks and diluted serially in tenfold steps with the diluent mentioned above. The diluted samples were spread on various agar media prepared by the procedures of Mitsuoka et al [12], and cultured by the methods described previously [13]. The bacterial count per gram of specimen was estimated from the colony count on each agar medium.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation